Timing of Hip-fracture Surgery in Elderly Patients: Literature Review and Recommendations - Seong, Yoon Jae (Hip Pelvis, 2020)
The incidence of hip fractures is rapidly increasing with an aging population and is now one of the most important health concerns worldwide due to a high mortality rate. The effect of delayed surgery on postoperative outcomes has been widely discussed. Although various treatment guidelines for hip fractures in the elderly exist, most institutions recommend that operations are conducted as soon as possible to help achieve the most favorable outcomes. While opinions differ on the relationship between delayed surgery and postoperative mortality, a strong association between earlier surgery and improvement in postoperative outcomes (e.g., length of hospital stay, bedsore occurrence, return to an independent lifestyle), has been reported. Taken together, performing operations for hip fractures in the elderly within 48 hours of admission appears to be best practice. Importantly, however, existing evidence is based primarily on observational studies which are susceptible to inherent bias. Here, we share the results of a literature search to summarize data that helps inform the most appropriate surgical timing for hip fractures in the elderly and the effects of delayed surgery on postoperative outcome. In addition, we expect to be able to provide a more accurate basis for these correlations through a large-scale randomized controlled trial in the future and to present data supporting recommendations for appropriate surgical timing.